1996
DOI: 10.1144/gsl.sp.1996.109.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Model study of the influence of matrix shrinkage on absolute permeability of coal bed reservoirs

Abstract: The matrix volume of coal shrinks when occluded gases desorb from its structure. In coalbed gas reservoirs, matrix shrinkage could cause the fracture aperture width to increase, causing an increase in permeability. A computer model was developed, based on elastic rock mechanics principles, to evaluate the potential effect of matrix shrinkage on the absolute permeability of coalbed reservoirs as fluid pressure is drawn down during gas production. The model predicts that the fracture width can potentially increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
238
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(262 citation statements)
references
References 13 publications
9
238
1
Order By: Relevance
“…19 The above equation can then be rewritten as It has also been shown that for isotropic media, the volumetric strain can be closely approximated by three times the linear strain. 20 On a large scale, coal is not isotropic because of its layered characteristic, but on a small (matrix block) scale, there is evidence that coal behaves in an isotropic manner and that linear strain in all directions is equivalent to onethird of the volumetric strain, 21 which supports the assumption that coal is an isotropic medium on a small scale. Substituting linear strain ( lm ) for one-third the volumetric strain results in the following equation: Sorption-Induced Strain.…”
Section: Factors That Affect Cleat Widthmentioning
confidence: 94%
See 2 more Smart Citations
“…19 The above equation can then be rewritten as It has also been shown that for isotropic media, the volumetric strain can be closely approximated by three times the linear strain. 20 On a large scale, coal is not isotropic because of its layered characteristic, but on a small (matrix block) scale, there is evidence that coal behaves in an isotropic manner and that linear strain in all directions is equivalent to onethird of the volumetric strain, 21 which supports the assumption that coal is an isotropic medium on a small scale. Substituting linear strain ( lm ) for one-third the volumetric strain results in the following equation: Sorption-Induced Strain.…”
Section: Factors That Affect Cleat Widthmentioning
confidence: 94%
“…For example, porosity, sorption- 6 Young et al 24 Sawyer et al 4 Gash 25 Levine 21 Palmer and Mansoori 6 Gray 3 Seidle et al 9 Shi and Durucan 8 0.339 Young's modulus, E, psi 300,000 to 600,000 124,000 to 445,000 392,000 500,000…”
Section: Sensitivity Of Model To Input Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorption of gases on coal results in matrix deformation, a well-accepted phenomenon in CBM research community. Several researchers [Levine, 1996;Harpalani and Mitra, 2010] have proposed a Langmuir-type model to fit the volumetric strain, given as follows:…”
Section: Effect Of Sorption-induced Strainmentioning
confidence: 99%
“…(20) for selected cleat volume compressibility values. The range of E (2,000 to 4,000 MPa) and  (0.2 to 0.4) reported by Levin (1996) is adopted here.…”
Section: Constant Confining Pressure Vs Uniaxial Strain Conditionmentioning
confidence: 99%